2021
DOI: 10.3389/fendo.2021.613826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dosage Reduction of Hypoglycemic Multidrug Regimens on the Incidences of Acute Glycemic Complications in People With Type 2 Diabetes Who Fast During Ramaḍān: A Randomized Controlled Trial

Abstract: ObjectiveWe aimed to investigate the effect of dosage reduction of four hypoglycemic multidrug regimens on the incidences of acute glycemic complications in people with type 2 diabetes who fast during Ramaḍān.MethodsWe conducted an open-label, parallel-group, randomized controlled trial at a tertiary care center in Amman, Jordan. We recruited adults with type 2 diabetes who expressed an intention to fast during Ramaḍān and were adherent to one of four regimens—namely: metformin and glimepiride; metformin and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Three studies (two RCTs) out of four demonstrated that insulin dosage reduction of between 25 and 40% TDD decreases rates of hypoglycemia for some participants ( 23 , 24 , 28 ). The average hypoglycemic incidence rate from these two RCTs was 22.5% [21.4% in Shehadeh et al ( 23 ), 23% in Zaghlol et al ( 24 )] in the control group and 4.5% [4.8% from Shehadeh et al ( 23 ), 4.2% in Zaghlol et al ( 24 )] in the intervention group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies (two RCTs) out of four demonstrated that insulin dosage reduction of between 25 and 40% TDD decreases rates of hypoglycemia for some participants ( 23 , 24 , 28 ). The average hypoglycemic incidence rate from these two RCTs was 22.5% [21.4% in Shehadeh et al ( 23 ), 23% in Zaghlol et al ( 24 )] in the control group and 4.5% [4.8% from Shehadeh et al ( 23 ), 4.2% in Zaghlol et al ( 24 )] in the intervention group.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (two RCTs) out of four demonstrated that insulin dosage reduction of between 25 and 40% TDD decreases rates of hypoglycemia for some participants ( 23 , 24 , 28 ). The average hypoglycemic incidence rate from these two RCTs was 22.5% [21.4% in Shehadeh et al ( 23 ), 23% in Zaghlol et al ( 24 )] in the control group and 4.5% [4.8% from Shehadeh et al ( 23 ), 4.2% in Zaghlol et al ( 24 )] in the intervention group. Another study compared premixed twice-daily dosing to short-acting insulin at iftar with intermediate at suhur (the meal consumed early in the morning before dawn and before fasting commences) and found no difference in hypoglycemia ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations